2014
DOI: 10.2174/0929867321666140706142335
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial Dysfunction: The Link Between Homocysteine and Hydrogen Sulfide

Abstract: High level of homocysteine (hyperhomocysteinemia, HHcy) is associated with increased risk for vascular disease. Evidence for this emerges from epidemiological studies which show that HHcy is associated with premature peripheral, coronary artery and cerebrovascular disease independent of other risk factors. Possible mechanisms by which homocysteine causes vascular injury include endothelial injury, DNA dysfunction, proliferation of smooth muscle cells, increased oxidative stress, reduced activity of glutathione… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
139
0
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 194 publications
(145 citation statements)
references
References 137 publications
1
139
0
5
Order By: Relevance
“…Al-Magableh and Hart (2011) and Hedegaard et al 2014)). As a result of these studies, H 2 S is often described as a "potent vasodilator" (Bhatia 2005;Pushpakumar et al 2014;Ariyaratnam et al 2013;Jang et al 2014;Baragatti et al 2013;Ghasemi et al 2012) despite data clearly showing otherwise. However, the addition of GYY4137 at concentrations and incubation times which deliver nM to low μM H 2 S also leads to vasodilation in vitro and in vivo (Table 1) suggesting blood vessels are acutely sensitive to small fluxes of H 2 S when it is generated in a manner and a level comparable to enzymatic (e.g.…”
Section: Gyy4137: Vascular Effectsmentioning
confidence: 99%
“…Al-Magableh and Hart (2011) and Hedegaard et al 2014)). As a result of these studies, H 2 S is often described as a "potent vasodilator" (Bhatia 2005;Pushpakumar et al 2014;Ariyaratnam et al 2013;Jang et al 2014;Baragatti et al 2013;Ghasemi et al 2012) despite data clearly showing otherwise. However, the addition of GYY4137 at concentrations and incubation times which deliver nM to low μM H 2 S also leads to vasodilation in vitro and in vivo (Table 1) suggesting blood vessels are acutely sensitive to small fluxes of H 2 S when it is generated in a manner and a level comparable to enzymatic (e.g.…”
Section: Gyy4137: Vascular Effectsmentioning
confidence: 99%
“…Among these, endothelial dysfunction is pivotal in the initiation and development of atherosclerosis [1, 2]. Homocysteine (Hcy)is an independent risk factor for atherosclerosis, and is thought to contribute to endothelial dysfunction through Hcy-induced cell injury [3]. The mechanism for Hcy-induced endothelial cell injury is not clear, but several studies have demonstrated that it involves autophagy [4].…”
Section: Introductionmentioning
confidence: 99%
“…Hcy is a sulfur-containing, nonprotein-forming amino acid synthesized from the normal biosynthesis of methionine and cysteine, and is an important intermediate in the one-carbon pathway. 25 We classified patients as having HHcy when Hcy levels exceeded the normal limit. The damaging effects of HHcy on endothelial function are, at least in part, through the inhibition of endothelial nitric oxide synthase, which produces endoplasmic reticulum stress.…”
Section: Discussionmentioning
confidence: 99%